EFEKTIVITAS FASILITASI PENYEDIAAN PUPUK BERSUBSIDI KABUPATEN MANGGARAI TIMUR UNTUK USAHATANI PADI SAWAH - Hardi, Dionisius Jusember; Sutiknjo, Tutut Dwi; Sidhi, Eko Yuliarsha (Universitas Kadiri, 2023)
Provision of food as a basic need for Indonesian citizens is a strategic role of the agricultural sector. The government continues to encourage increased farming activities by facilitating the provision of subsidized fertilizers for farmers. This activityis intended as an incentive for farmers to increase productivity. In practice, facilitating the provision of subsidized fertilizers is not always effective. The research was focused on rice production centers in East Manggarai Regency, precisely in LambahLeda Utara District, namely Satar Padut Village. Primary data was obtained from interviews with 24 farmers, 2 agricultural shop owners who were distributors, and employees of the local Food Crops Agriculture Office. This research employeddescriptive qualitative in presenting the results. The effectiveness of facilitating the provision of subsidized fertilizers in Satar Padut Villagewas measured by four indicators, which consistedof price accuracy, quantity, time of availability, and type of fertilizer. The research results showedthat the four indicatorswere not yet effective.The price of fertilizer sold to farmers above the highest retail price, besides,therewas still a shortage of fertilizer, and the type of fertilizer distributedwas not in accordance with government recommendations and the allocation of subsidized fertilizerwas not timely.Penyediaan pangan sebagai kebutuhan pokok warga Indonesia merupakan peran strategis sektor pertanian. Pemerintah terus mendorong peningkatan kegiatan usaha tani melalui fasilitasi penyediaan pupuk bersubsidi bagi para petani. Kegiatan ini ditujukan sebagai insentif bagi petani dalam peningkatan produktivitas. Dalam prakteknya, fasilitasi penyediaan pupuk bersubsidi tidaklah selalu efektif. Penelitian difokuskan di sentra produksi padi Kabupaten Manggarai Timur, tepatnya di Kecamatan Lambah Leda Utara, yaitu Desa Satar Padut. Data primer diperoleh dari hasil wawancara kepada 24 petani, 2 pemilik toko pertanian yang merupakan distributor, dan pegawai Dinas Pertanian Tanaman Pangan setempat. Penelitian menggunakan deskriptif kualitatif dalam memaparkan hasil. Efektivitas fasilitasi penyediaan pupuk bersubsidi di Desa Satar Padut yang diukur dari empat indikator, yang terdiri atas ketepatan harga, kuantitas, waktu ketersediaan, dan jenis pupuk. Hasil penelitian menunjukan bahwa keempat indikator tersebut belum efektif. Hal ini dapat dilihat dari harga pupuk yang dijual kepada para petani di atas harga eceran tertinggi, selain itu masih terjadi kelangkaan pupuk, dan jenis pupuk yang didistribusikan tidak sesuai dengan anjuran pemerintah serta pengalokasian pupuk bersubsidi tidak tepat waktu.